2 & 4.This is just logic.I don't know to show calculation involving in it.
2007-02-15 23:47:15
·
answer #1
·
answered by Vinu 3
·
0⤊
0⤋
Oh come on. If you have to ask a question, then at least make it a good one, not an auto answer to some fourth grade homework problem. Here's some hints for next time:
1) Look in the back af the math textbook. It's called the glossary, g-l-o-s-s-a-r-y
2) Ask someone. For pete's sake, you have parents for a reason.
3) Try to figure it out. On a scale of 1-10, this is a sqtrt(-1). muahahahah
4) Give up and ask your teacher next day. The 100% doesn't mean anything if you cheat and then fail the next test. Better to know it.
That asking a computer is your first step is a sad note on the progress of our society. All of the above suggestions take less time to do than posting and getting answers to a question. I want to be ther when you power goes out in a storm and your precious computer is gone. Ha.
Just so you're happy, its 2 and 4. Two numbers totalling six, well that's either 5+1, 2+4, 3+3. Least common multiple means that both the numbers can go into four. thus, 2+4=6, LCM =4
2007-02-15 10:20:38
·
answer #2
·
answered by John Doe IV 3
·
0⤊
0⤋
First no is 2
Second no is 4
lcm=4
Sum=2+4=6
Thank You
2007-02-15 11:21:16
·
answer #3
·
answered by Manu M 1
·
0⤊
0⤋
The numbers are 2 and 4.LCM of 2 and 4 is 4.Their sum is 6.
2007-02-16 03:21:41
·
answer #4
·
answered by ♦Opty misstix♦ 7
·
0⤊
0⤋
Since the LCM is 4,The larger of the two numbers must be 4,because the only other smaller numbers are:1,2,&3.all primes.
And hence since one number is 4 and the sum is 6,the other number is 6-4=2.
Hence the numbers are :2 & 4. (Answer)
{2+4=6;and LCM of 2 & 4 is 6] (Proved)
2007-02-16 07:25:37
·
answer #5
·
answered by AMIT B 1
·
2⤊
0⤋
2 and 4.
lcm of 2 and 4 is 4.
2+4=6.
2007-02-15 18:39:50
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
the numbers are 4 and 2
2007-02-18 03:00:03
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
x+y=6
xy=hcf*lcm
Find out the hcf of 6 and 4 which is 2.
Therefore, xy=2*4=8
or, y=8/x
Putting the value of y in the first eqn, we get
x+8/x=6
=> x^2+8=6x
=> x^2-6x+8=0
Solve the quadric eqn
x=(-b+/-sqrt(b^2-4ac)/2a
=> x=(6+/-sqrt(36-32))/2
=> x=(6+/-sqrt(4))/2
=> x=(6+/-2)/2
=> x=2 and 4
Hope you are happy now.
2007-02-15 20:56:14
·
answer #8
·
answered by Bishu 3
·
0⤊
1⤋
first no is 2& second no is 4.
2007-02-15 22:32:06
·
answer #9
·
answered by amit y 1
·
0⤊
0⤋
2+4=6 and 2,4
2007-02-17 02:43:37
·
answer #10
·
answered by DEEPU 1
·
0⤊
0⤋